Segregation and expression analyses of hyaluronan‐binding protein 2 (HABP2): insights from a large series of familial non‐medullary thyroid cancers and literature review. (23rd March 2017) - Colombo, Carla; Muzza, Marina; Proverbio, Maria Carla; Ercoli, Giulia; Perrino, Michela; Cirello, Valentina; Vicentini, Leonardo; Ferrero, Stefano; Fugazzola, Laura
Summary: Introduction: Recently, the G534E variant of the HABP2 gene was reported as the underlying genetic defect in a large kindred with nonsyndromic familial nonmedullary thyroid cancer (FNMTC). Nevertheless, this postulated role was not confirmed in additional cohorts. Contrasting data are also available on HABP2 expression in the thyroid. Objectives: To investigate HABP2 as a potential susceptibility gene in a large series of 27 unrelated families with FNMTC and to test its expression in thyroid tumour and matched normal tissues. Results: Three of the 27 FNMTC families (11·1%) carried the HABP2 G534E variant. The genotyping of these families showed that HABP2 G534E does not segregate with cancer. Indeed, affected individuals not carrying HABP2 G534E were identified, and the variant was present also in members without thyroid cancer. HABP2 mRNA had a very variable expression in tissues from FNMTC, sporadic papillary thyroid cancers (PTCs) or contralateral normal tissues, by either nonquantitative or quantitative RT‐polymerase chain reaction. In almost all cases, the gene appeared down‐ or up‐regulated in tumours with respect to the corresponding normal tissue. At immunohistochemistry, HABP2 was expressed in both tumour and matched control tissues, without differences between sporadic and familial cases. Conclusions: This study on a wide series of FNMTC indicates that the HABP2 G534E variant is frequent, but does not segregate with the disease. Nevertheless, the dysregulation of HABP2 expression found in either sporadic or familial PTCs or normal thyroid tissues is consistent with similar findings in other malignancies and could indicate a role of this gene also in thyroid cancer.